2005
DOI: 10.1021/ja056498s
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically Controlled Synthesis of Triangular and Hexagonal Nanoplates of Palladium and Their SPR/SERS Properties

Abstract: The rapid reduction of Na(2)PdCl(4) by ethylene glycol in the presence of poly(vinyl pyrrolidone) (PVP) has recently been demonstrated as a convenient method of generating Pd cubooctahedra and twinned nanoparticles. Here we describe a new procedure where Pd triangular or hexagonal nanoplates could be selectively synthesized by manipulating the reduction kinetics of the polyol process. More specifically, the reduction rate was substantially reduced through the introduction of Fe(III) species and the O(2)/Cl(-) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
513
0
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 654 publications
(557 citation statements)
references
References 59 publications
21
513
0
8
Order By: Relevance
“…The FFT patterns observed in Figs.5(c) and (d) agree with that in Fig.5(b), which means that a single crystalline dendrite was produced. The result agrees with that of the leaf part structure, which is observable only for a sample that is atomically smooth and very thin two dimensional flat sheets [7,15,29,30].…”
Section: Spectral Characterizations Of Ag Nanostructuressupporting
confidence: 86%
“…The FFT patterns observed in Figs.5(c) and (d) agree with that in Fig.5(b), which means that a single crystalline dendrite was produced. The result agrees with that of the leaf part structure, which is observable only for a sample that is atomically smooth and very thin two dimensional flat sheets [7,15,29,30].…”
Section: Spectral Characterizations Of Ag Nanostructuressupporting
confidence: 86%
“…It was reported that the twinned Pd particles could be selectively removed and produced uniform, single-crystal cubooctahedra Pd nanoparticles by controlling the Cl − /O 2 etching process. 52 In the present process, the Cl The experiments presented above have shown that the addition of certain amount of iodine ions into the polyol process to realize the kinetic control of the reaction rate is the prerequisite for the formation of Pt nanoflowers.…”
Section: Resultsmentioning
confidence: 84%
“…Ethylene glycol has been identified as unique in serving as both the solvent and the primary reductant for Pt nanocrystal synthesis. 16,111,112 It has also been recognized that the kinetics of crystal growth can be controlled by reducing agents. For example, a strong reducing agent may assist in the formation of thermodynamically favoured polyhedral nanocrystals.…”
Section: Developments Of the Synthetic Methodsmentioning
confidence: 99%